THE IMPORTANCE OF DISTANCE LEARNING IN HIGHER EDUCATION - Feruza Boymurodova Ziyotqizi; Munisabonu Qosimova (Western European Studies, 2024)
Distance learning has emerged as a transformative force in higher education, democratizing access to knowledge and catering to diverse learning styles. This article explores the burgeoning role of distance learning in the contemporary academic landscape, highlighting its potential to expand educational opportunities. However, the implementation of effective distance learning programs necessitates acknowledging inherent challenges. This article delves into a critical examination of these challenges, including fostering student engagement in a virtual environment, ensuring equitable access to technology and resources, and cultivating a sense of community among geographically dispersed learners. To address these obstacles, the article proposes a multi-pronged approach. It emphasizes the importance of interactive learning platforms that promote active participation, robust student support systems that address individual needs, and the development of a strong online learning community that fosters collaboration and connection.By critically examining the opportunities and challenges associated with distance learning, this article aims to contribute to the ongoing discourse on optimizing educational delivery in the digital age. It argues that through the strategic implementation of innovative pedagogical practices and a commitment to student support, distance learning can fulfill its transformative potential in higher education
Keywords: distance learning; technical difficulties; online education mode